2007
DOI: 10.1038/sj.bjc.6604081
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear translocation of haeme oxygenase-1 is associated to prostate cancer

Abstract: The role of oxidative stress in prostate cancer has been increasingly recognised. Acute and chronic inflammations generate reactive oxygen species that result in damage to cellular structures. Haeme oxygenase-1 (HO-1) has cytoprotective effects against oxidative damage. We hypothesise that modulation of HO-1 expression may be involved in the process of prostate carcinogenesis and prostate cancer progression. We thus studied HO-1 expression and localisation in 85 samples of organ-confined primary prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
118
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(131 citation statements)
references
References 49 publications
12
118
1
Order By: Relevance
“…HO-1 has long been identified as proto-oncogenic due to its anti-apoptotic and pro-angiogenic properties (54,55), and there is a positive relationship between high nuclear HO-1 content and severity of prostate cancer (35), Nonetheless, the precise role of HO-1 in cancer biology is far from being completely understood. Cancer cells display altered metabolic circuitry and nutrient uptake to increase proliferation preferentially, leading to glucose-dependent ATP production (Warburg theory).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HO-1 has long been identified as proto-oncogenic due to its anti-apoptotic and pro-angiogenic properties (54,55), and there is a positive relationship between high nuclear HO-1 content and severity of prostate cancer (35), Nonetheless, the precise role of HO-1 in cancer biology is far from being completely understood. Cancer cells display altered metabolic circuitry and nutrient uptake to increase proliferation preferentially, leading to glucose-dependent ATP production (Warburg theory).…”
Section: Discussionmentioning
confidence: 99%
“…Each of these columns was then incubated for 10 min individually with 20 l of 35 S-labeled Nrf2 and fragments (⌬C1-⌬C4). The columns were then washed with copious amounts of phosphate buffer.…”
Section: Expression and Purification Of Recombinant Gst Fusion Ho-1-fmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated that ageing, genetic predisposition, androgen hormone levels, dietary factors, inflammation and oxidative stress play crucial role in the initiation and development of PC. Oxidative stress in the development of PC has been under intensive research [4].…”
Section: Introductionmentioning
confidence: 99%